Habitat specialisation controls ectomycorrhizal fungi above the treeline in the European Alps. Issue 5 (30th November 2020) - Arraiano‐Castilho, Ricardo; Bidartondo, Martin I.; Niskanen, Tuula; Clarkson, James J.; Brunner, Ivano; Zimmermann, Stephan; Senn‐Irlet, Beatrice; Frey, Beat; Peintner, Ursula; Mrak, Tanja; Suz, Laura M.
Summary: Alpine habitats are one of the most vulnerable ecosystems to environmental change, however, little information is known about the drivers of plant–fungal interactions in these ecosystems and their resilience to climate change. We investigated the influence of the main drivers of ectomycorrhizal (EM) fungal communities along elevation and environmental gradients in the alpine zone of the European Alps and measured their degree of specialisation using network analysis. We sampled ectomycorrhizas of Dryas octopetala, Bistorta vivipara and Salix herbacea, and soil fungal communities at 28 locations across five countries, from the treeline to the nival zone. We found that: (1) EM fungal community composition, but not richness, changes along elevation, (2) there is no strong evidence of host specialisation, however, EM fungal networks in the alpine zone and within these, EM fungi associated with snowbed communities, are more specialised than in other alpine habitats, (3) plant host population structure does not influence EM fungal communities, and (4) most variability in EM fungal communities is explained by fine‐scale changes in edaphic properties, like soil pH and total nitrogen. The higher specialisation and narrower ecological niches of these plant–fungal interactions in snowbed habitats make these habitats particularly vulnerable to environmental change in alpine ecosystems.